The Effect of Slow Deep Breathing and Progressive Muscle Relaxation on Blood Pressure in Hypertensive Patients in Kedaung Wetan Health Center Tangerang - Marlin Brigita; Ratu Shiba Arofah; Toto Subiakto (Hypertension Prevention and Control Research Center, The Polytechnic of Health of Banten, 2023)
Slow and deep breathing and progressive muscle relaxation are non-pharmacological therapies that are easy to do. This therapy can make the body more relaxed so that it can lower blood pressure. This study aims to determine the effectiveness of slow deep breathing therapy and progressive muscle relaxation in reducing blood pressure in hypertensive patients. This research uses a quasi-experimental design with a one-group research design using a pre-test and post-test approach without a control group. Respondents in this study consisted of 16 hypertensive patients selected by purposive sampling, with one intervention group. The intervention was carried out by the respondent, who performed slow and deep breathing techniques and progressive muscle relaxation through the media provided. The results showed a significant difference in blood pressure before and after instruction in deep breathing techniques and progressive muscle relaxation, using the paired t-test. The results of the analysis using the t-test showed that there was a significant influence between slow deep breathing techniques and progressive muscle relaxation on blood pressure in hypertensive patients (p-value < 0.05). Therefore, it is hoped that nurses can optimize slow and deep breathing techniques and progressive muscle relaxation as non-pharmacological therapies for managing patient hypertension.